Contrasting effector profiles between bacterial colonisers of kiwifruit reveal redundant roles converging on PTI‐suppression and RIN4. Issue 4 (20th March 2023) - Jayaraman, Jay; Yoon, Minsoo; Hemara, Lauren M.; Bohne, Deborah; Tahir, Jibran; Chen, Ronan K. Y.; Brendolise, Cyril; Rikkerink, Erik H. A.; Templeton, Matthew D.
Summary: Testing effector knockout strains of the Pseudomonas syringae pv. actinidiae biovar 3 (Psa3) for reduced in planta growth in their native kiwifruit host revealed a number of nonredundant effectors that contribute to Psa3 virulence. Conversely, complementation in the weak kiwifruit pathogen P. syringae pv. actinidifoliorum (Pfm) for increased growth identified redundant Psa3 effectors. Psa3 effectors hopAZ1a and HopS2b and the entire exchangeable effector locus ( ΔEEL ; 10 effectors) were significant contributors to bacterial colonisation of the host and were additive in their effects on virulence. Four of the EEL effectors (HopD1a, AvrB2b, HopAW1a and HopD2a) redundantly contribute to virulence through suppression of pattern‐triggered immunity (PTI). Important Psa3 effectors include several redundantly required effectors early in the infection process (HopZ5a, HopH1a, AvrPto1b, AvrRpm1a and HopF1e). These largely target the plant immunity hub, RIN4. This comprehensive effector profiling revealed that Psa3 carries robust effector redundancy for a large portion of its effectors, covering a few functions critical to disease.